2022
DOI: 10.3390/foods11050720
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Yeast Wickerhamomyces anomalus in Biocontrol of Gray Mold Decay of Tomatoes and Study of the Mechanisms Involved

Abstract: Gray mold decay is a widespread postharvest disease in tomato that results from infection by the pathogen Botrytis cinerea, leading to huge economic losses. The objective of this study was to select the most effective antagonistic yeast to control tomato gray mold from six potential biocontrol agents and to investigate the possible control mechanism. The results showed that the yeast Wickerhamomyces anomalus was the most effective in inhibiting B. cinerea among the six strains both in vivo and in vitro on toma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…For example, the yeast Wickerhamomyces anomalus increased the activity of antioxidant enzymes POD, ascorbate peroxidase (APX) and SOD, and promoted the biosynthesis of total phenols and flavonoids, resulting in disease resistance to B. cinerea in postharvest tomatoes. 51 p-Coumarate esters promoted the accumulation of chlorogenic acid and catechin, which enhanced the disease resistance of apple fruit to B. cinerea. 52 Chitosan induced a jasmonic acid-dependent defense response in B. cinerea-infected strawberries that was based on the accumulation of phenolics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the yeast Wickerhamomyces anomalus increased the activity of antioxidant enzymes POD, ascorbate peroxidase (APX) and SOD, and promoted the biosynthesis of total phenols and flavonoids, resulting in disease resistance to B. cinerea in postharvest tomatoes. 51 p-Coumarate esters promoted the accumulation of chlorogenic acid and catechin, which enhanced the disease resistance of apple fruit to B. cinerea. 52 Chitosan induced a jasmonic acid-dependent defense response in B. cinerea-infected strawberries that was based on the accumulation of phenolics.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have indicated that the accumulation of phenolics in postharvest fruit enhances their disease resistance to B. cinerea infection. For example, the yeast Wickerhamomyces anomalus increased the activity of antioxidant enzymes POD, ascorbate peroxidase (APX) and SOD, and promoted the biosynthesis of total phenols and flavonoids, resulting in disease resistance to B. cinerea in postharvest tomatoes 51 . p ‐Coumarate esters promoted the accumulation of chlorogenic acid and catechin, which enhanced the disease resistance of apple fruit to B. cinerea 52 .…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study suggest that the increase in abundance of the first three may be caused by the accumulation of a large number of pathogens due to the increase in the number of years of colonization of peach trees. Some representative species of Metschnikowia ( Sipiczki, 2020 ; Wang et al, 2021 ), Wickerhamomyces ( Lanhuang et al, 2022 ), and Geotrichum ( Kawtharani et al, 2022 ) have been shown to be antagonistic to various pathogens and can be widely used as biocontrol agents in organic agriculture. T. delbrueckii in the genus Torulaspora has been reported to be able to produce phytase under certain conditions, increasing the nutritional content of peach and improving the absorption of trace elements in peach by humans ( Kaur et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous reports on the applications of antagonistic yeasts in postharvest biological control of various fruits including apple [ 22 ], pear [ 23 ], banana [ 24 ], kiwifruit [ 25 ], citrus [ 14 ], grape [ 26 ], papaya [ 27 ], as well as strawberry [ 28 ], and pineapple [ 29 ]. Additionally, the use of antagonist yeasts for the biocontrol of vegetables such as potatoes [ 30 ], tomatoes [ 31 ] and chilies [ 32 ] has been extensively documented. Moreover, antagonist yeasts have also been employed in controlling mold in grains, which are prone to mycotoxin contamination [ 33 ].…”
Section: Biocontrol Of Yeasts In Agricultural Productsmentioning
confidence: 99%